PELAKSANAAN PENINGKATAN KEPATUHAN PELAPORAN LAPORAN HARTA KEKAYAAN PENYELENGGARA NEGARA (LHKPN) (Universitas Teknologi Muhammadiyah Jakarta (UTM Jakarta), 2018)
This study aims to test and analyze the Implementation of Enhancing the Compliance of Reporting the Statutory Assets of State Assets (LHKPN) in the Scope of Regional Agencies at the Directorate of Registration and Examination of LHKPN. In this study the authors used a Qualitative Descriptive Data analysis method using the Interative Analysis model. The author uses the Triangulation technique to test the validity of the data that has been obtained during the study.Â Purposive Sampling Method is a sample determination technique with certain considerations. The results of the research prove that the level of LHKPN Reporting Compliance in the Scope of Regional Agencies has decreased from 2016-2017. This percentage can still increase if it is supported by the role and awareness of the Obligatory Report to report their assets and the commitment of the Regional Head / Head of Institution related to the application of sanctions for compulsory reporting who do not report LHKPN to the KPK. The next level of LHKPN Reporting Compliance in the Bangka Belitung Islands Provincial Government in 2017 has increased. Because since the beginning the Governor of the Bangka Belitung Islands Provincial Government has committed in the framework of preventing corruption, one of them is by reporting the LHKPN and issuing the Bangka Belitung Islands Governor Regulation No. 56 of 2017 concerning Management of State Organizer Asset Management in the Province of Bangka Belitung Provincial Government and issuing Circular Number : 840/0098 / VII / 2018 dated April 3, 2018 concerning the delay in payment of the Income Improvement Allowance (TPP).